Analisis Tingkat Kepuasan Masyarakat terhadap jasa pelayanan Pelabuhan Penyeberangan di Provinsi Sulawesi Tenggara - Asriyati, Asriyati; Hado, Hado; Sufrianto, Sufrianto; Satyadharma, Maudhy (Universitas Sulawesi Tenggara, 2023)
This research wants to examine the level of public satisfaction with the services provided by the Southeast Sulawesi Provincial Transportation Service through its service units. The research implementation was only focused on 4 Ferry Port UPTDs, namely the Baubau-Waara Ferry Port UPTD, the Torobulu-Tampo Ferry Port UPTD, the Amolengo-Labuan Ferry Port UPTD and the Kendari-Langara Ferry Port UPTD, where the implementation time took place from March-August 2023. The research sample was 384 passengers who had received services at the 4 UPTD ferry ports. The research results concluded that the level of community satisfaction was 77,050 or in the good category.